Sedentary behavior and physical activity are associated with risk of depression among adult and older populations: a systematic review and dose–response meta-analysis - Wang, Dawei; Zhang, Yuheng; Guo, Zhiguang; Lu, Songtao (Frontiers in Psychology, 2025)
BackgroundDepression symptoms are commonly experienced by adults and older people; however, there is uncertainty concerning the associations of lifestyle with the risk of depression. This study systematically reviewed and meta-analyzed observational data to assess the link between instrumented sedentary behavior (i-SB) and physical activity (i-PA) measures and depression risk among adult and older populations.MethodsA systematic review across four databases was performed up to July 27, 2024, targeting studies linking i-SB, i-PA, and depression. The review included a dose–response meta-analysis, presenting results as odds ratios (OR) and 95% confidence intervals (95% CI).ResultsFifty-one studies, encompassing 1,318,687 participants, fulfilled the inclusion criteria. The comparison between the most and least sedentary groups yielded a pooled OR of 1.09 (95% CI 1.05–1.13). The comparison between the least and most active participant groups yielded pooled ORs of 0.96 (95% CI 0.93–0.98) for light activity (LPA), 0.91 (95% CI 0.86–0.96) for moderate-to-vigorous activity (MVPA), 0.93 (95% CI 0.90–0.96) for total physical activity (TPA), and 0.87 (95% CI 0.81–0.94) for steps per day. After adjusting i-PA, a lower OR for i-SB did not indicate a significant link to increased depression risk. Meta-regression analyses confirmed a dose–response relationship between SB, MVPA, daily steps, and depression.ConclusionThe association between i-SB and the risk of depression was not consistent with the results of previous self-reported studies. MVPA linked to the risk of depression was independent of i-SB, whereas the link between i-SB and the risk of depression was not independent of i-PA.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=546666, identifier CRD42024546666.